ETHICS MEETS INTELLIGENCE: RETHINKING VALUES EDUCATION IN THE AGE OF ARTIFICIAL INTELLIGENCE (UNIZIK Journal of Educational Management and Policy, 2025)
As Artificial Intelligence (AI) becomes increasingly integrated into education, it changes not only how students learn but also the value system they must navigate. This paper explores the growing need to rethink values education in response to the ethical challenges posed by AI. Traditional moral instruction, while still valuable, is insufficient for addressing issues such as data privacy, surveillance, and questions surrounding authorship and intellectual ownership. The study underscores the importance of equipping students with ethical reasoning skills, critical thinking, and AI literacy to prepare them for responsible digital citizenship. It highlights how AI, though beneficial in personalizing learning and improving efficiency, can also perpetuate discrimination and erode trust if used without ethical oversight. By integrating digital ethics across curricula and promoting cross-disciplinary teamwork among educators, technologists, and ethicists, schools can better prepare students for the complexities of the AI age. The study recommended embedding ethics in STEM education, promoting early and continuous ethical education, involving community stakeholders, and establishing national policies to ensure responsible AI use.
Keywords: Ethics, Values Education, Artificial Intelligence, Rethinking Education, Ethical Values